Combinations of select menhaden fish meal and spray-dried plasma protein in the transition diet (11 to 15 lb) for the early-weaned pig - J R Bergstrom; K Q Owen; W B Nessmith Jr; B T Richert; J W Smith II; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1995)
Early-weaned pigs (weaned at 7 to 14 d of age) that are managed in a conventional, one-site production system require a more complex diet in the transition phase (11 to 15 lb) than early-weaned pigs that are managed in a segregated early weaning (SEW), multiple-site, production system.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Pigs; Growth performance; Fish meal; Plasma